FROM THE HISTORY OF THE CREATION AND MANAGEMENT OF THE GOVERNOR-GENERAL OF TURKESTAN. - Mardieva Yulduz Ubaidullaevna (Scholar Express Journals, 2021)
The next study is devoted to the process of the emergence of the Turkestan Governor-General as a result of the conquest of the Central Asian states by the Russian Empire in the middle of the 19th century. The Russian Empire pursued a well-thought-out policy in order to consolidate its dominance in the country and, most importantly, to preserve the colonial chain for a long time. This process is also evident in the system of government introduced only by imperial officials. This is due to the fact that historically established traditional systems of government were undermined, and the system was developed and implemented in practice, which meets the interests of the empire and at the same time completely contradicts the worldview of the local population
Keywords: Turkestan; khanates; emirates; empire